2014
DOI: 10.1080/17290376.2014.976250
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between economic empowerment and sexual behaviour and practices of migrant workers within the context of HIV and AIDS in the Lesotho textile industry

Abstract: Economic empowerment brings with it a wide range of consequences, both positive and negative. The objective of this paper was to examine the relationship between economic empowerment and the sexual behaviour and practices of migrant workers within the context of HIV and AIDS in the Lesotho textile industry. Data for this paper were extracted from the findings of a larger study which had been conducted concerning HIV and AIDS in the textile industry in Lesotho. Using in-depth interviews, data were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…( 2010 ) addressed both economic and health impacts of caregiving to orphans and results revealed that there were significant transfers of funds from the government and families to older adults caring for orphans, but the older adults still had health and financial problems as a result of taking care of their ill children. Studies on community reaction related to older aged caregivers and their families (Knodel, Williams, Kim, Puch, & Saengtienchai, 2010 ; Tanga & Tangwe, 2014 ; Tanyi & Okoye, 2014 ) revealed a mixture of positive and negative reactions present but that positive support from others in the community was often dominant. This finding is contrary to common portrayals that predominantly emphasis the negative aspects associated with HIV/AIDS (Li et al., 2008 ; Møller & Erstad, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…( 2010 ) addressed both economic and health impacts of caregiving to orphans and results revealed that there were significant transfers of funds from the government and families to older adults caring for orphans, but the older adults still had health and financial problems as a result of taking care of their ill children. Studies on community reaction related to older aged caregivers and their families (Knodel, Williams, Kim, Puch, & Saengtienchai, 2010 ; Tanga & Tangwe, 2014 ; Tanyi & Okoye, 2014 ) revealed a mixture of positive and negative reactions present but that positive support from others in the community was often dominant. This finding is contrary to common portrayals that predominantly emphasis the negative aspects associated with HIV/AIDS (Li et al., 2008 ; Møller & Erstad, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Migration has been shown to be a key risk factor for HIV acquisition in populations around the world [13]. However, different types of migrating populations are not homogenous in their risk profiles.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Uganda, Kenya, and Lesotho, studies have shown that young women increased supply of sex to acquire luxury goods, such as mobile phones and high-priced clothing [10, 29], but had greater choice whether to use a condom or engage in sex or not when earning salary through employment [76]. In Nigeria, a study also found that attempts to mitigate food deprivation partly explained slum adolescent girls’ engaging in risky sexual behaviors [77].…”
Section: Discussionmentioning
confidence: 99%
“…The observation that men have more non-sexual opportunities to earn income has been documented in Mozambique and Haiti [28, 78], and was also described among our youth in Kenya. There has been some evidence as well suggesting that young men in Lesotho increased demand for sex partners once obtaining employment or income [76], and that economic hardship for Zimbabwean men diminished their capacity to support sexual relationships [79]. Research has also shown that while cost barriers persist in accessing discounted and free male condoms among low-wage users [21, 80], the cost of female condoms is approximately twelve times greater than male ones and often unaffordable for low-income consumers who find them acceptable to use [81].…”
Section: Discussionmentioning
confidence: 99%